Reciprocal Teaching Style and Motivation in Improving Learning Outcomes of Deep Foot Passing in Football Courses - AR, Sahabul Adri; ., Samsudin; Humaid, Hidayat (KnE Social Sciences, 2024)
Teaching style is one of the supporting factors for success in learning. Every teacher (teacher/lecturer), must pay attention and choose a teaching style that is in accordance with the material that will be given to students. It is known that there are problems in Penjaskesrek students at Serambi Mekkah University, including the low average score of students in football courses. Based on the results of the analysis, this happens because students underestimate this course, so it looks like students are not excited and can even be categorized as less motivated. The formulation of the problem in this study is whether there is an effect of reciprocal teaching style and motivation on improving learning outcomes of deep foot passing in football courses. This study aimed to determine the effect of reciprocal teaching style and motivation on improving learning outcomes of deep foot passing in football courses. This research is an experimental research, with a population of 40 students. The sampling technique in this study is total sampling. Based on the results of the study, it was found that there was an effect of the reciprocal learning model and motivation on improving the learning outcomes of passing the inner leg in soccer courses, namely the high motivation group, the average pre-test 46.4 increased by 14.95 so that it became an average of 61.35. While, the low motivation group, the pre-test average of 46.7 increased by 13.85 so that it became an average of 60.55. In conclusion, to improve the learning outcomes of passing in football, especially inner foot passing, students who have high or low motivation can use a reciprocal learning model. Keywords: reciprocal, passing, football